Faktor - Faktor yang Mempengaruhi Biaya CSR Pada Perusahaan Transportation & Logistic - Lucky, Della; Grania Mustika, Ira; Astarani, Juanda (Jurnal Akuntansi Terapan dan Bisnis, 2024)
Transportation companies are one of the dominant sectors contributing to the largest negative impact of greenhouse gas emissions in Indonesia. CSR is carried out to reduce these negative impacts, but the company's economic dynamics influence the costs incurred. This research examines the factors that influence CSR costs while adding to the limited literature related to dependent variables. This research method is quantitative through documentation. Researchers used secondary data from annual and sustainability reports of transportation & logistics sector companies listed on IDX for the 2020-2023 period. The sampling technique uses purposive sampling. Multiple linear regression analysis was carried out using SPSS 26. The research results are profitability, leverage, market capitalization and company size simultaneously influence CSR costs. Meanwhile, separately, the profitability does not have an influence, each of the market capitalization and leverage have a negative influence, and the company size has a positive influence on CSR costs.